Offshore wind and solar complementarity in Brazil: A theoretical and technical potential assessment. (15th October 2022) - de Souza Nascimento, Marcolino Matheus; Shadman, Milad; Silva, Corbiniano; de Freitas Assad, Luiz Paulo; Estefen, Segen F.; Landau, Luiz
Abstract: The onshore generation of wind and solar energy is a reality in Brazil. There are approximately 700 projects generating wind energy in the Northeast and South regions and 4000 generating solar energy distributed throughout the country. In addition, Brazil has an extensive Exclusive Economic Zone (EEZ) and a very diverse climate, which can contribute to offshore and complementary technologies. The concept of complementarity integrates technology and innovation studies, which are associated with the more efficient use of renewable resources through a better understanding of their intermittency and availability. This study aims to evaluate the complementarity of offshore wind and solar energy along the Brazilian coastline by assessing the theoretical and technical potential of the resources. Wind and solar radiation hourly data of the ERA5 reanalysis are used from 1990 to 2019. A series of technical and environmental restrictions and other uses of the ocean space is assumed to calculate the usable area. The IEA-15 MW wind turbines and crystalline silicon solar panels are considered to calculate annual energy production and capacity factor. The results show the annual and hourly complementarity of the offshore wind and solar energy sources. It is observed that, for instance, offshore solar complements offshore wind up to 40% in the Northeast region within water depth up to 50 m. Additionally, it shows that the monthly energy production of a co-located offshore wind–solar farm in the Northeast region can reach up to 300% more than the hydropower generation. Highlights: Offshore wind–solar complementarity along the Brazilian coastline is assessed. Estimation of technical potential of offshore wind–solar in different water depths. Daily complementarity of offshore wind by solar reaches up to 40% in Rio de Janeiro. Offshore wind–solar electricity generation exceeds the hydropower in the Northeast. The Significant potential of offshore wind–solar in water depths up to 20 m.